2022
DOI: 10.1021/acsearthspacechem.2c00092
|View full text |Cite
|
Sign up to set email alerts
|

Possible Effects of Ozone Chemistry on the Phase Behavior of Skin Oil and Cooking Oil Films and Particles Indoors

Abstract: Heterogeneous reactions occurring between ozone and films or particles containing skin oil or cooking oil can be a sink of ozone and a source of organic compounds indoors with negative health effects. To predict this heterogeneous chemistry, information on the phase behavior (number and types of phases) within these films and particles, and its evolution during ozone exposure, is needed. In this work, we used optical microscopy to directly observe the phase behavior of proxies for skin oil and cooking oil part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…64,65 The formation of a new semisolid or solid phase has recently been observed for squalene and skin oil proxy particles that have been exposed to high concentrations of ozone. 66 However, due to uncertainties in the exact mechanism that causes the slower squalene decay, such potential surface crust formation and associated kinetic limitations are not treated in the model. We can also speculate that such a burial process may be affected by temperature and may be different on room surfaces compared to human skin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…64,65 The formation of a new semisolid or solid phase has recently been observed for squalene and skin oil proxy particles that have been exposed to high concentrations of ozone. 66 However, due to uncertainties in the exact mechanism that causes the slower squalene decay, such potential surface crust formation and associated kinetic limitations are not treated in the model. We can also speculate that such a burial process may be affected by temperature and may be different on room surfaces compared to human skin.…”
Section: Resultsmentioning
confidence: 99%
“…AIOMFAC simulations also predicted that the addition of acids to the mixture, such as present in skin oil, could cause LLPS and lead to the formation of surface crusts that can limit partitioning and multiphase reaction kinetics. 81,82 Further experimental validations as well as simulations with more realistic skin oil compositions including other unsaturated fatty acids and triglycerides 83 are required to further improve our understanding on skin ozonolysis and its impacts on indoor air quality.…”
Section: Discussionmentioning
confidence: 99%
“…We then considered recent work by the Bertram group, who reported that liquid squalene and skin oil exposed to ozone form a new condensed phase composed of oligomeric ozonolysis products . These higher-molecular-weight oligomers could show increased hydrophobicity compared to unreacted squalene and skin oil, but the optical microscopy data reported by the Bertram group indicate them to be inside of the imaged sample drops.…”
Section: Resultsmentioning
confidence: 99%
“…The role of “sorbed” or interfacial water may be important, as the heterogeneous oxidation of squalene has been shown to produce gas-phase ozonolysis products with compositions varying with relative humidity . Just like in an outdoor atmospheric secondary organic aerosol, which can transition from having honey-like viscosity at high humidity to marble-like viscosity at low humidity, , water molecules may also act as a plasticizer in indoor surface layers, films, and materials. Experiments geared toward quantifying the amount of water uptake, for instance, by quartz crystal microbalance mass estimations or linear and nonlinear spectroscopy are therefore needed to further understand how the heterogeneous ozonolysis of human skin oil and its constituents forms a material with increased hydrophobicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation